Photopigment, Absorption, and Growth Responses of Marine Cryptophytes to Varying Spectral Irradiance. Issue 2 (13th February 2020) - Heidenreich, Kristin M.; Richardson, Tammi L.
Abstract : The underwater light field of lakes, estuaries, and oceans may vary greatly in spectral composition. Phytoplankton in these environments must contain pigments that absorb the available colors of light. If spectral quality changes, acclimation to the new spectral environment would confer an ecological advantage in terms of photosynthesis and growth. Here, we explored the capacity of eight marine cryptophytes to adjust pigmentation in response to changes in spectral irradiance and related effects on light absorption, photosynthetically useable radiation (PUR), and growth rate. The pigment composition of all species changed in some way in response to shifts in spectral irradiance, but not all pigment changes could be considered advantageous in the context of chromatic acclimation. For most species, absorption by chl‐ a and chl‐ c 2 resulted in highest absorption in the blue region, highest PUR values for blue‐light grown cells, and highest growth rates in blue light. The exception was Chroomonas mesostigmatica (CCMP 1168), which contains a high percentage of Cryptophyte‐Phycocyanin (Cr‐PC) 645, absorbs strongly in the orange‐to‐red region of the spectrum, and grew fastest under red light. The position and magnitude of the maximum and secondary absorption peak of Cr‐PC 569, the phycobiliprotein pigment of Hemiselmis cryptochromatica, varied with spectral irradiance. The underlying cause remains unknown, but may represent a mechanism by which cryptophytes optimize photon capture.